Effectiveness of the YEARS Algorithm Added to Classical Clinical Decision-making Rules in Suspected Pulmonary Embolism - Handan Özen Olcay; Şeref Kerem Çorbacıoğlu; Emine Emektar; Yunsur Çevik (Global Emergency and Critical Care)
Objective: Pulmonary embolism (PE) is usually non-specific in terms of symptoms and signs and needs to be confirmed by an objective test. Pulmonary computed tomography angiography (PCTA) has been widely used for diagnosis in recent years. Our aim was to evaluate the potential of the YEARS algorithm to reduce the need for PCTA compared with the classical algorithm. Materials and Methods: This prospective observational study. Between 15.03.2018 and 15.09.2019, patients admitted to the emergency department with suspected PE who underwent PCTA according to the classical algorithm (Wells) were included in the study. YEARS criteria were reviewed according to the patients’ files and general laboratory results without knowing the results of PCTA. The need for PCTA was investigated according to classical clinical decision-making rules and YEARS algorithms. Results: The study included 300 patients. According to YEARS, 69% of patients required PCTA, whereas 31% required the YEARS PE exclusion group. According to YEARS, PE was detected in 16.4% of patients with an indication for PCTA, whereas only 2.2% of patients in the PCTA exclusion group had PE. In the patient cohort that included the “probable PE” group according to the Wells, the sensitivity according to the YEARS was 94.4%. Conclusion: In this study, the YEARS protocol used in addition to the classical algorithm resulted in a 31% reduction in the need for PCTA. However, we also showed that the YEARS algorithm may be insufficient for the diagnosis of low rate, positive PE.